Post-mortem forensic identity testing: application of PCR to the identification of fire victim - Soares-Vieira, José Arnaldo; Billerbeck, Ana Elisa Correia; Iwamura, Edna Sadayo Miazato; Cardoso, Laís de Almeida; Muñoz, Daniel Romero (São Paulo Medical Journal, 2000)
CONTEXT: DNA analysis has been used with success in the identification of carbonized corpses and victims of large accidents. The analysis requires relatives of crash victims to donate blood for analysis. The relatives are generally willing contribute to the identification by giving a blood sample. OBJECTIVE: To describe the use of the polymerase chain reaction (PCR) for genetic characterization of one victim extensively burned by fire. DESIGN: Case report. CASE REPORT: DNA was extracted from blood of the cardiac chamber, and 15 different loci (D1S80, ApoB, D17S30, D3S1744, D18S849, D12S1090, FGA, D7S820, D1S533, D9S304, HUMCSF1PO, HUMTPOX, HUMTHO1, amelogenin and HLA-DQA1) were analyzed using the PCR technique. Results from all loci typing of the corpse were then compared to that of his alleged biological parents, revealing a genetic compatibility.